2022
DOI: 10.18502/tbsrj.v4i2.9662
|View full text |Cite
|
Sign up to set email alerts
|

Is there an Association between Side Effects of AstraZeneca, Sputnik, Covaxin and Sinopharm COVID-19 vaccines and Breakthrough Infections?

Abstract: Introduction: Safe and efficacious vaccines against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), would contribute to contain the COVID-19 pandemic. In this study, we examined this question that if there is an association between the incidence of side effects and the COVID-19 breakthrough infections. Material and Methods: This descriptive-analytical cross-sectional study was conducted for two months from June 22 to August 22, 2021. The study method was complete enumeration and 1474 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Moreover, abnormal bleeding was mostly experienced in the two weeks post-vaccination, which extends beyond the typical 7 days for the adverse symptoms monitoring established in vaccine trials, as observed by Lee et al [25]. Similar percentages of vaccinated women experiencing MCD was found in this and other studies [20,28], independently of their previous history of SARS-CoV-2 infection. For their part, Li et al [35] conclude that the average sex hormone concentrations and the ovarian reserve did not significantly change in those COVID-19 women of child-bearing age who experienced self-resolve menstrual changes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, abnormal bleeding was mostly experienced in the two weeks post-vaccination, which extends beyond the typical 7 days for the adverse symptoms monitoring established in vaccine trials, as observed by Lee et al [25]. Similar percentages of vaccinated women experiencing MCD was found in this and other studies [20,28], independently of their previous history of SARS-CoV-2 infection. For their part, Li et al [35] conclude that the average sex hormone concentrations and the ovarian reserve did not significantly change in those COVID-19 women of child-bearing age who experienced self-resolve menstrual changes.…”
Section: Discussionsupporting
confidence: 85%
“…To date, there are few available data about the link between SARS-CoV-2 vaccine and MC in menstruating people [14,16,17,[20][21][22][23][24][25][26][27][28]. Furthermore, the prevalence of this event in formerly menstruating people remains unknown, because different causes of secondary amenorrhea − pregnancy, breastfeeding, menopause, contraceptives methods, and gynecological conditions [29,30] -has been considered as exclusion criteria in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…1). Para evaluar la calidad metodológica de estos artículos se identificó el diseño metodológico, lo que dio como resultado 17 artículos de tipo observacional a los que se aplicó la pauta STROBE y un ensayo clínico al que se aplicó la Escala de Jadad 5,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . En la aplicación de la pauta STROBE, el ítem que menos se cumplió fue el de «validez externa»; estos estudios no especificaban si los resultados podrían ser extrapolados a una población distinta o a otros escenarios de mayor magnitud 13,14,18,20,23,24,26,27 .…”
Section: Resultsunclassified
“…Many women across the world after receiving COVID vaccines are repining of irregularities in their menstrual bleeding; some experiencing heavy menstrual bleeding (menorrhagia), some bleeding before their periods were due or bleeding frequently (metrorrhagia/polymenorrhagia), whereas some are complaining of postmenopausal bleeding [ 6 , 13 ]. By comparing the six vaccine types in 6 Arabic countries, a higher percentage of menstrual irregularity was observed in Johnson & Johnson, followed by Sinopharm, Moderna, and AstraZeneca.…”
Section: Discussionmentioning
confidence: 99%